Phase III, randomized, double‐blind, placebo‐controlled study to evaluate the efficacy and safety of teneligliptin monotherapy in Chinese patients with type 2 diabetes mellitus inadequately controlled with diet and exercise. Issue 4 (20th September 2020) - Ji, Linong; Ma, Jianhua; Lu, Weiping; Liu, Jingdong; Zeng, Jiao'e; Yang, Jialin; Li, Wei; Zhang, Xiuzhen; Xiao, Xinhua; Takayanagi, Gen; Wang, Yi
Abstract: Aims/Introduction: Although the efficacy of teneligliptin, a highly selective dipeptidyl peptidase‐4 inhibitor, has been amply studied for the treatment of type 2 diabetes, no clinical trials of teneligliptin have been carried out in China. We evaluated the efficacy and safety of teneligliptin monotherapy compared with a placebo in Chinese patients with type 2 diabetes mellitus inadequately controlled with diet and exercise. Materials and Methods: This multicenter, randomized, double‐blind, placebo‐controlled, parallel‐group study, carried out at 42 sites, enrolled type 2 diabetes patients with glycosylated hemoglobin 7.0 to <10.0% and fasting blood glucose <270 mg/dL. Patients were randomly assigned, in a 1:1 ratio, to treatment with 20 mg teneligliptin or a placebo ( n = 127, each) administered orally once daily before breakfast for 24 weeks. Change in glycosylated hemoglobin from baseline to week 24 was the primary efficacy end‐point. Safety was assessed by the incidence of adverse events and adverse drug reactions. Results: The least square mean (LSM) change in glycosylated hemoglobin from baseline to week 24 was −0.95% with teneligliptin versus −0.14% with a placebo, yielding an LSM difference (teneligliptin vs placebo) of −0.80% ( P < 0.0001). For the secondary end‐point, from baseline to week 24, the LSM change in fasting blood glucose was −21.9 mg/dL with teneligliptin versus −1.4 mg/dL with a placebo, yielding an LSM difference (teneligliptin vs placebo) of −20.5 mg/dL ( P < 0.0001). The adverse event and adverse drug reaction incidence rates, including hypoglycemia, were similar in both groups. Conclusions: At 24 weeks, teneligliptin was generally well tolerated and effective in Chinese patients with type 2 diabetes mellitus inadequately controlled with diet and exercise. Abstract : This multicenter, randomized, double‐blind, placebo‐controlled, parallel‐group study evaluated the efficacy and safety of teneligliptin monotherapy compared with a placebo in Chinese patients with type 2 diabetes mellitus inadequately controlled with diet and exercise. To assess efficacy (primary efficacy end‐point: glycosylated hemoglobin from baseline to week 24) and safety (incidence of adverse events and adverse drug reactions), eligible type 2 diabetes patients were assigned in a 1:1 ratio to treatment with teneligliptin 20 mg or a placebo, administered orally once daily before breakfast for 24 weeks. The least square mean change in glycosylated hemoglobin from baseline to week 24 was −0.95% with teneligliptin versus −0.14% with a placebo, and the least square mean change in fasting plasma glucose from baseline to week 24 was −21.9 mg/dL with teneligliptin versus −1.4 mg/dL with a placebo, with the incidence rates of adverse events and adverse drug reactions being similar in both groups, showing that teneligliptin was effective and generally well tolerated at 24 weeks among Chinese patients with type 2 diabetes inadequately controlled with diet and exercise.